Analysis of Article 433 of the Civil Code: Dilemma of Persons with Disabilities in Carrying Out Legal Acts - Agustini, Shenti; Agustianto, Agustianto; Jaya, Febri (Universitas Medan Area, 2024)
The provisions of Article 433 of the Civil Code contain phrases that violate the rights of people with disabilities, especially for people with non-permanent mental disabilities. Through this provision, people with permanent mental disabilities are prevented from carrying out legal actions. This research aims to analyze the skills of people with disabilities in carrying out legal actions and analyze the provisions of Article 433 of the Civil Code with the Constitution. The research method used is normative juridical. In formulating the answer to the problem, a juridical basis and a theoretical basis are used. The research results show that the provisions of Article 433 have discriminated against people with non-permanent mental disabilities and it has been declared through the Constitutional Court Decision that Article 433 is conditionally unconstitutional. The challenge is that the district court as an institution that has the authority to form pardons must be truly careful and careful in making decisions/decisions on requests for pardons. Therefore, it is necessary to evaluate the implementation of these institutions on an ongoing basis to ensure that people with disabilities receive protection for their rights as people with disabilities.